1985
DOI: 10.1007/bf00496370
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of GABA by bovine adrenal medulla slices

Abstract: A sodium dependent GABA uptake system has been found in bovine adrenal medulla slices. This uptake has a Km of 83.19 +/- 38.45 microM and a Vmax of 9.20 +/- 1.36 pmol/min X mg of tissue. It was inhibited by nipecotic acid and 2,4-diaminobutyric acid (IC50 67 and 38.5 microM, respectively) but not by beta-alanine at concentrations up to 5 mM, a result which is similar to those found for the neuronal GABA uptake rather than the glial uptake. It is suggested that GABA uptake together with catabolic action of GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Clear elevations in [Ca 2+ ] i were observed in response to application of etomidate as low as 1 μ m . Chromaffin cells can release GABA upon stimulation (Kataoka et al 1984; Oset Gasque et al 1985, 1990) which raises the possibility that etomidate potentiated the response to endogenously released GABA. We believe this possibility to be unlikely, but not impossible, as the cells were continuously perfused and there were small numbers of cells in a relatively large bath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear elevations in [Ca 2+ ] i were observed in response to application of etomidate as low as 1 μ m . Chromaffin cells can release GABA upon stimulation (Kataoka et al 1984; Oset Gasque et al 1985, 1990) which raises the possibility that etomidate potentiated the response to endogenously released GABA. We believe this possibility to be unlikely, but not impossible, as the cells were continuously perfused and there were small numbers of cells in a relatively large bath.…”
Section: Discussionmentioning
confidence: 99%
“…GABA plays an important role in the physiology of the adrenal medulla: (1) chromaffin cells possess the enzymes that synthesize and degrade GABA (Fernandez‐Ramil et al 1983; Kataoka et al 1984); (2) GABA is taken up by chromaffin cells and released in response to depolarizing stimuli (Kataoka et al 1984; Oset Gasque et al 1985, 1990); (3) GABA‐immunoreactive nerve fibres are found throughout the adrenal medulla (Kataoka et al 1986; Oomori et al 1993) and bundles of GABA immunoreactive nerve fibres run into the medulla with varicosities often in close contact with chromaffin cells (Kataoka et al 1986; Oomori et al 1993); and (4) chromaffin cells express GABA A receptors (Bormann & Clapham, 1985; Amenta et al 1988; Peters et al 1989). Functionally it has been shown that GABA can elicit catecholamine release from isolated perfused adrenal glands (Sangiah et al 1974; Kataoka et al 1984; Kitayama et al 1984; Fujimoto et al 1987; Gonzalez et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In previous work we also described characteristics of a potent GABA uptake system in both bovine adrenal medulla slices (Oset-Gasque et al, 1985) and in bovine chromaffin cells in culture (Oset-Gasque and Aunis, 1989). This uptake process could have an important role in the termination of GABA action on chromaffin cells secretory activity.…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, y-aminobutyric acid (GABA) systems are present in adrenal medulla glands (Fernandez-Ramil el al., 1982, 1983Kataoka et al, 1984;Oset-Gasque et al, 1985;Gonzalez et al, 1987). Several authors have found that GABA influences CA release from both adrenal medulla (Kataoka et al, 1986; and chromaffin cells in culture (Kataoka et al, 1984(Kataoka et al, , 1986.…”
Section: Introductionmentioning
confidence: 99%